Peningkatan Kemampuan Pemecahan Masalah dan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Problem Posing (PTK Siswa Kelas X AP 2 SMK Prawira Marta Kartasura Tahun Ajaran 2016/2017) - Hayati, Titik Nur, Rita Pramujiyanti Khotimah,S.Si, M.Sc (2017)
The purpose of this study is to enhance the problem solving and learning outcomes mathematics student of class X AP 2 in SMK Prawira Marta Kartasura through the application of problem posing models. This study includes classroom action research. Students of class X AP 2 SMK Prawira Marta Kartasura as recipients act and mathematics teachers as act master and researchers as an observer. Method of collection, data in this research are observation, field note, teacher interview, problem solving test and student achievement test and documentation. Technique of analyzing data as a data reduction, data presentation, and conclusion. The results showed an increased ability to problem-solving visits of indicators many students are able: 1) Understanding the problem before action 13students (36%) after treatment 28 students (76,35%) 2) Develop a plan before the action 12 students (33%)after treatment29 students(79,15%) 3) Implement the plan prior to the action29 students (41%)after the action of30 students(81,9%). There was also an increase in students' mathematics learning outcomes seen from the achievement of students score ≥ KKM (minimum completeness criteria) of 11 students (30%) increased to 29 students (80,5%).Based on the study, it was concluded that the learning model of problem posing in mathematics, can improve problem-solving and learning outcomes of mathematics student.